Evaluation of microalgae diets for the spat of mangrove oyster Crassostrea rhizophorae (Güilding, 1828) and its growth in outdoor conditions - Glem, María E.; Freites, Luis Felipe; Guevara, Miguel; Márquez, Adrián; Lodeiros, César (AquaTechnica, 2020)
In order to guarantee an adequate level of macromolecular reserves, and allow their successful transfer to the natural environment, we have studied the survival, growth and biochemical composition (carbohydrates, lipids and proteins) of the spat (initial length 3.77 ± 0.64 mm) of the mangrove oyster Crassostrea rhizophorae, fed with seven different combinations (diets) of three tropical microalgae: Chaetoceros sp. Araya strain (Ch-A), Isochrysis galbana (Ig) and Tetraselmis chui (Tc). The microalgae biochemical composition was also determined. In the indoor bioassay, each one of the seven diets was assigned three aquariums (replicates with 21 spat). In addition, three more replicates were arranged in an outdoor environment (control). After 36 days, the biochemical and biometric parameters of the juveniles in the indoor bioassay were determined, and they were transferred to the outdoor environment. The control treatment suffered considerably high mortality rates (≈80%) during this period and it was not possible to obtain further data from it for the experiment. The transferred juveniles continued to be cultured in suspension for 30 days, after which their biochemical and biometric parameters were evaluated again. During this period, samplings of the environmental variables were taken weekly. In general, within the indoor period, the greatest biometric and biochemical values were obtained in the organisms fed with one monoalgal diet (Ch-A), bialgal diets (Ch-A+Tc; Ch-A+Ig) and the trialgal diet (Ch-A+Ig+Tc), a tendency that remained in the outdoor environment. This was attributed to the balanced contribution of biomolecules previously offered by these diets. These results suggest that the juveniles made use of the energy content found in carbohydrates and lipids once they were transferred outdoors; where these energy sources were probably catabolized to compensate for the scarce availability of food (low chlorophyll a and organic seston) observed in the outdoor culture site.